Exclusive Breastfeeding Practice and Associated Maternal Socio-Demographic Factors among Mothers Attending Imo State Specialist Hospital, Owerri, South-Eastern Nigeria - Chikere Ifeanyi Casmir Ebirim; Ugonma Winnie Dozie; Wanwuri Akor; Ijeoma Judith Dozieand Oluchi Agatha Ashiegbu (Archives of Community Medicine and Public Health - Peertechz Publications, 2016)
Introduction: Breast milk is unique and contains the entire nutritional requirement a new born infants needs for the first year of life. Exclusive breastfeeding is defined as the consumption of no other food or liquids except breast milk and drops or syrups consisting of vitamin-mineral supplements or medicines for at least 4 months and if possible the first 6 months of life. The aim of this study was to determine the socio-demographic factors associated with exclusive breastfeeding practice in Imo specialist hospital, Owerri, south-eastern Nigeria. Methods: A cross sectional survey was adopted for this study and 450 randomly selected mothers of infants who visited Imo State Specialist Hospital for post-natal care were recruited for the study. A structured questionnaire was used to collect information on socio-demographic characteristics and infant exclusive breastfeeding pattern. Only mothers who gave their consent were recruited and confidentiality of information was maintained throughout the study period. Result: The result indicated that majority of the mothers 192 (42.7%) were aged between 25 - 29 years and 225 (50%) attained tertiary education. Most of the mothers were either trader 167(37.1%) or civil  servant (36.0%). The result indicated that 78 (17.3%) of the mothers exclusively breastfed their baby's for at least 4 months, while only 27 (6.0%) of the mothers exclusively breastfed their infants for up 6 months. Initiation of breast milk to infant revealed that 174 (38.7%) of the mothers initiated breastfeeding less than an hour after delivery, 150 (33.3%) initiated breastfeeding within 2 - 24 hrs. Socio-demographic factors associated with exclusive breastfeeding practice (4 - 6 months) includes age (χ2 = 28.8149, p < 0.001), educational attainment (χ2 = 7.6934, p < 0.021) and average monthly income (χ2 = 30.8472, p < 0.001). Conclusion: In view of the findings of this study, Mothers should be well informed about the benefits of exclusive breastfeeding on the child. Health care providers should also be trained on the principles of exclusive breastfeeding so that they can inform mothers on the best way to practice exclusive breastfeeding. Government should make policies to extend the period of maternity leave from 3 months to 6 months as this will help employed mothers achieve a complete exclusive breastfeeding practice and reduce the problem of child morbidity and mortality in Owerri in particular and Nigeria in general.